Endothelium-Derived Hyperpolarizing Factor and Myoendothelial Coupling: The in vivo Perspective - Schmidt, Kjestine; de Wit, Cor (Frontiers in Physiology, 2020)
The endothelium controls vascular tone adopting blood flow to tissue needs. It releases chemical mediators (e.g. NO, prostaglandins) and exerts appreciable dilation through smooth muscle hyperpolarization, thus termed endothelium-dependent hyperpolarization (EDH). Initially, EDH was attributed to release of a factor, but later it was suggested that smooth muscle hyperpolarization may be derived from radial spread of an initial endothelial hyperpolarization through heterocellular channels coupling these vascular cells. The channels are indeed present and formed by connexins that enrich in gap junctions. In vitro data suggest that myoendothelial coupling underlies EDH-type dilations as evidenced by blocking experiments as well as simultaneous, merely identical membrane potential changes in endothelial and smooth muscle cells which is indicative of coupling through ohmic resistors. However, connexin-deficient animals do not display any attenuation of EDH-type dilations in vivo and endothelial and smooth muscle cells exhibit distinct and barely superimposable membrane potential changes exerted by different means in vivo. Even if studied in the exact same artery EDH-type dilation exhibits distinct features in vitro and in vivo: In isometrically mounted vessels, it is rather weak and depends on myoendothelial coupling through connexin40, whereas in vivo as well as in vitro under isobaric conditions it is powerful and independent of myoendothelial coupling through Cx40. It is concluded, that EDH-type dilations are distinct and a significant dependence on myoendothelial coupling in vitro does not reflect the situation under physiologic conditions in vivo. Myoendothelial coupling may act as a backup mechanism that is uncovered in the absence of the powerful EDH-type response and possibly reflects a situation in a pathophysiologic environment.